The Analysis of Complaint Expressions Used by the Eighth Semester Students of English Education Program of Purworejo Muhammadiyah University in the Academic Year of 2016/2017 - Yanuar Dwi Cahyo (Scripta : English Department Journal, 2019)
This research is aimed to describe the complaint strategies and to discover what the dominantcomplaint strategy used by the eighth semester students of English Education Program ofPurworejo Muhammadiyah University in the academic year of 2016/2017. This research is adescriptive qualitative research, the researcher uses ODCT (Oral Discourse Completion Test) asthe instrument of the research. The research result shows that the participants expressed thespeech act of complaint in eight complaint strategies: Hints, Annoyances, Ill Consequences,Indirect Accusation, Direct Accusation, Modified Blame, Explicit Blame (Behaviour), and ExplicitBlame (Person). In the Situation 1 (Professor Situation), most of the participants frequentlyused the weakest level of complaint strategy namely Hints (50%). In the Situation 2 (Classmatesituation), most of the participants frequently used more aggressive level of complaint strategythan the first situation, namely Direct Accusation (36.7%). In the Situation 3 (Juniors Situation),it is found that the participants highly used Modified Blame (33.3%) which is the strongest levelof complaint strategy. This investigation of speech acts has the potential to improveinterpersonal communication in multicultural societies.